Supply Demand Ratio and Water Utilization Index in Jurala Project Command Area, Andhra Pradesh, India - Neelima, T. L.; Ramana, K. V.; Reddy, M. Devender; Devi, M. Uma; Ramulu, V.; Ramanjaneyulu, A. V. (International Journal of Bio-resource and Stress Management, 2014)
The Priyadarsini Jurala Project (PJP) is a multipurpose project constructed across the river Krishna, near Revulapalli village, mainly designed to irrigate low water requirement crops in the drought prone area of Mahabubnagar district, Andhra Pradesh. The irrigation performance assessment of any project is judged using performance indicators. Hence, the performance indicators namely supply demand ratio and water utilization index (WUI) were calculated, which will help to know whether water supplied is based on timely crop irrigation demand and also if the irrigation performance is appropriate at all the reaches in the command area. Crop area was monitored using two years remotely sensed (RS) data of IRS P6 LISS-III and AWiFs sensor. The principal crop grown in the command area during kharif season was paddy (0.0234 mha), of which 37.2% of the area was under right canal and 62.8% was under left canal. The monthly net irrigation requirement (NIR) of remote sensing derived cropping pattern was calculated for RMC and LMC using CROPWAT model. The calculated monthly supply-demand ratio showed that the irrigation supply was more than demand. The WUI was low for left canal as compared to the right canal.